The first spontaneous spawning of red drum Sciaenops ocellatus L. in Europe: broodstock management and early larval stages - Mariateresa Lastilla (Italian Journal of Animal Science, 2015)
The present paper reports a research on reproductive parameters and larval rearing of red drum (Sciaenops ocellatus) maintained in captivity for the first time in Europe. Red drum juveniles were obtained from United States in the late 90s. In early January 2013, 40 in total male and female red drums ranging from 34 to 47 cm in length were held in a 25 m3 rectangular tank with a closed recirculating system with a water flow of 6000 L/h, located in Lesina (FG) fish farm (Southern Italy). Water temperature and salinity ranged between 21.0 and 28.8°C and from 25 to 27 g/L respectively. The fish were fed commercial feed pellet (46% protein) at 1.1% of body weight daily. Sexual maturation occurred during the natural breeding season of red drum. Approximately 43 spawns were recorded by the end of July and continuing to mid-September, with mean number of 66.5 millions of eggs collected overall on spawn period. Batch fecundity (3.325*106 ova per female) and relative fecundity (361.41 ova/g body weight) were calculated. Fertilisation rate was 30 to 80%. Larvae were hatched at a mean total length of 2.40±0.33 mm and showed a gradual increase in size of approximately 0.378 mm/day for the first 40 day after hatching (DAH). Cannibalism was observed as larger larvae preyed on smaller ones; to limit the phenomenon red drum population was selected for size at 35 DAH. Reliable information on fecundity and larval stage is essential for encouraging Sciaenops ocellatus farming also in Mediterranean countries.